How Does a Worker's Labour Market History Affect Duration? - Johnston, D; Borland, J (Melbourne, 2010)
This study explores the relation between a worker’s job duration and prior labour market experience. Hazard models are estimated using data on employment spells for the population aged 25 to 64 years in Australia from the HILDA survey (waves 1 to 7). A worker’s labour force state immediately preceding an employment spell is found to have a significant effect on the likelihood of exit from employment, as well as the exit destination and whether the exit is involuntary. In particular, previously being unemployed or having experienced involuntary separation from a job is associated with worse subsequent employment outcomes. To develop further insights into the role of labour market history a hazard model for exit from unemployment is also estimated, and the results contrasted with those from the employment model.
Melbourne Institue of Applied Economics and Social Research Working Paper Series
Keywords: Employment -- Exit from employment (Retirement/Redundancy); Employment; Employment -- Unemployment; Employment -- Entry to employment; Ageing; Labour market; Employment; Unemployment; Exit from employment (Retirement/Redundancy); Entry to employment; Ageing; Employment and unemployment